European Social Policy and the Green Perspective - Akpınarlı, Çağlayan Koşal (My University, 2010)
Yeşiller 1960’lardan bu yana çevre ve sosyal politika gibi konuların AB politik alanında tartışılmasını sağlayarak AB polikalarının biçimlenmesine katkıda bulunmaktadır. Özellikle refah devletinin krizi ile Yeşiller AB içinde sosyal haklarının savunucusu olarak yer almaya devam etmişlerdir. Yeşiller temel olarak Avrupa Birliği’nin Pazar odaklı politikalarını eleştirir ve yeşil ıdeolojı çerçevesinde Avrupa politikalarına katkıda bulunmaya çalışmaktadır. Bu çalışmanın temel argümanı Avrupa Birliği sosyal hakların iyileştirilmesinde daha etkin bir rol alması ve refah devletinin krizine çözüm bulabilmesi için Yeşillerin katkısı kaçınılmaz bir gerekliliktir. Bu nedenle bu çalışmada Avrupa Birliği sosyal politikasında Avrupa Yeşillerinin katkısı incelenmeye çalışılmıştır ve Yeşiller’in ne ölçüde Sosyal Avrupa'nın ortaya çıkmasında katkıda bulunabileceğini anlamaya çalışmaktadır.

Since 1960s, green politics have affected the European integration process. The Greens make important contributions to the European politics by bringing some issues into the political arena to be discussed, concerning environment and social policy. The Greens mainly criticize the European Union’s (EU) market based policies, and try to contribute into European policies in the lights of green ideology. Especially with the crisis of welfare state, the Greens remain as the advocate of the social rights within the EU. The main argument of this study is that EU should take a leading role for the improvement of social rights to offer an effective solution for the crisis of welfare as Europe being the territory where the social policy is emerged and that contribution of Green perspective is essential for the development of sustainable European social policy. Thus this study aims to examine the European Greens’ contribution especially in the European social policy, and tries to understand to what extent the Greens can contribute in the emergence of Social Europe.
Keywords: Avrupa Birliği_Türkiye; Uluslararası İlişkiler